Analisis Bandwidth dengan Menggunakan Metode Network Development Life Cycle(NDLC) - Maria Jania Putri Loe; Benyamin Jago Belalawe (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
In today's digital era, the need for a stable and reliable internet network is crucial, especially for institutions such as the Central Bureau of Statistics of East Nusa Tenggara Province, which relies on connectivity to support data processing and transmission activities. Although the Central Bureau of Statistics of East Nusa Tenggara Province utilizes three Internet Service Providers (ISP) with a total speed of up to 300 Mbps, uneven bandwidth distribution between rooms remains an obstacle to supporting work productivity. This study aims to analyze and optimize bandwidth management at the Central Bureau of Statistics of East Nusa Tenggara Province using the Network Development Life Cycle (NDLC) method. Through the NDLC stages, the network system is designed in a structured manner from analysis to maintenance. Data traffic management is carried out using MikroTik devices with the implementation of Quality of Service (QoS) and Queue Tree to ensure fair and efficient bandwidth distribution according to the needs of each work unit